2019
DOI: 10.1186/s12888-019-2401-3
|View full text |Cite
|
Sign up to set email alerts
|

Education level and risk of postpartum depression: results from the Japan Environment and Children’s Study (JECS)

Abstract: BackgroundLower socioeconomic status is often thought to be associated with an elevated risk of postpartum depression; however, this relationship exhibits noticeable heterogeneity between studies. The present study examined this relationship in Japan.MethodsData were obtained from 90,194 mothers in an ongoing birth cohort of the Japan Environment and Children’s Study. Socioeconomic status was assessed based on the mothers’ highest education level during pregnancy. Postpartum depression was identified at 1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
47
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 45 publications
13
47
2
2
Order By: Relevance
“…It is reported that cesarean section was associated with increased risk of postpartum depression [18]. Another study in Japan indicated that lower education level was associated with higher prevalence of postpartum depression and related symptoms [28]. Meanwhile, employment is considered as a protective factor for postpartum depression symptomatology [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that cesarean section was associated with increased risk of postpartum depression [18]. Another study in Japan indicated that lower education level was associated with higher prevalence of postpartum depression and related symptoms [28]. Meanwhile, employment is considered as a protective factor for postpartum depression symptomatology [29].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study from Japan, over 90,000 women were evaluated to find an association between education status and risk of developing PPD. The study revealed that higher education status among women was associated with a decreased rate of PPD [ 15 ]. The education level of a woman is frequently used to assess the socioeconomic status indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…What is interesting is that this work also demonstrated that in contrast with patients with higher education levels, illiterate ones did get affected by indoor daylight levels. Undoubtedly, the education levels of patients are often perceived as an adequate index for their socioeconomic status, apart from their income and occupation [21]. It has been proved that individuals with lower socioeconomic status tend to suffer from higher risks of psychiatric problems including depression, anxiety disorders and post-traumatic stress disorder [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%